Modern Lifestyle and Mental Health: An Observational Study Among Young Adults - Mustika, Ika; L, Sri Hidayati (International Conference on Sustainable Health Promotion, 2025)
Mental health is increasingly recognized as a global priority in the digital era. Recent data show that 6.2% of individuals aged over 15 years experience emotional mental disorders, often manifested as symptoms of anxiety. Lifestyle factors such as diet, physical activity, and sleep duration are thought to play a critical role in influencing anxiety risk. This study aimed to investigate the association between ultra-processed food consumption, physical activity, sleep duration, and anxiety disorders among young adults. A quantitative, cross-sectional design was applied with a total of 175 respondents aged 18–23 years. Data were analyzed using the chi-square test with a significance level of 0.05. The findings revealed no significant association between ultra-processed food consumption or physical activity and anxiety. However, sleep duration showed a significant association with anxiety (p = 0.031, <0.05). Insufficient sleep may contribute to dysregulation of stress hormones, thereby increasing the risk of anxiety disorders.